Photostable molecules on chip: A scalable approach to photonic quantum technologies - Colautti, M.; Mazzamuto, Giacomo; Cataliotti, F. S.; Lombardi, Pietro; Pazzagli, Sofia; Ovvyan, A. P.; Gruhler, N.; Pernice, W. H. P.; Kewes, G.; Neitzke, O.; Benson, Oliver; Toninelli, C. (Proceedings of the International School of Physics "Enrico Fermi", 2020)
In this manuscript we demonstrate the potential of a hybrid technology which combines single organic molecules as quantum light sources and dielectric chips. In particular, we discuss our approach based on evanescent coupling of dibenzoterrylene molecules to silicon nitride waveguides and show a coupling efficiency of up to 42 ± 2% over both propagation directions. Our results open a novel path towards a fully integrated and scalable photon processing platform.
CRIS-Team Scopus Importer:2023-04-20